Staff satisfaction in a long term care facility undergoing culture change - Knight, Kerri Lyn, author; Wood, Wendy, advisor; Sample, Pat, committee member; Vacha-Haase, Tammi, committee member (Colorado State University. Libraries, 2012)
An instrumental case-study look at perceptions of staff satisfaction at a long-term care facility undergoing the process of implementing culture change reforms was presented. Participants included CNAs, RNs and LPNs, managers, and therapists and therapy aides who participated in homogeneous and heterogeneous forum group discussions. Dissatisfaction was found in the work environment, breakdown of communication, and perceptions of leadership; satisfaction was found in enforcement of accountability, successful communication, suggestions for improvement and meaningful work experiences. The main conclusion was that the opportunities for empowerment are vital to staff members' experience of satisfaction; specifically, supporting staff authority and acknowledging effort, implementing systematic communication, cultivating positive relationships, and implementing staff suggestions to optimizing psychological benefits of the work experience.
Keywords: ability focused; staff satisfaction; person centered; long term care; culture change